Targeting functionalized nanoparticles to activated endothelial cells under high wall shear stress. Issue 2 (13th December 2019) - Zukerman, Hila; Khoury, Maria; Shammay, Yosi; Sznitman, Josué; Lotan, Noah; Korin, Netanel
Abstract: Local inflammation of the endothelium is associated with a plethora of cardiovascular diseases. Vascular‐targeted carriers (VTCs) have been advocated to provide focal effective therapeutics to these disease sites. Here, we examine the design of functionalized nanoparticles (NPs) as VTCs that can specifically localize at an inflamed vessel wall under pathological levels of high shear stress, associated for example with clinical (or in vivo) conditions of vascular narrowing and arteriogenesis. To test this, carboxylated fluorescent 200 nm polystyrene particles were functionalized with ligands to activated endothelium, that is, an E‐selectin binding peptide (Esbp), an anti ICAM‐1 antibody, or using a combination of both. The functionalized NPs were investigated in vitro using microfluidic models lined with inflamed (TNF‐α stimulated) and control endothelial cells (EC). Specifically, their adhesion was monitored under different relevant wall shear stresses (i.e., 40–300 dyne/cm 2 ) via real‐time confocal microscopy. Experiments reveal a significantly higher specific adhesion of the examined functionalized NPs to activated EC for the window of examined wall shear stresses. Moreover, particle adhesion correlated with the surface coating density whereby under high surface coating (i.e., ~10, 000 molecule/particle), shear‐dependent particle adhesion increased significantly. Altogether, our results show that functionalized NPs can be designed to target inflamed endothelial cells under high shear stress. Such VTCs underscore the potential for attractive avenues in targeting drugs to vasoconstriction and arteriogenesis sites.